Preparation of Anode Material for Lithium Battery from Activated Carbon - Sumrit Mopoung; Russamee Sitthikhankaew; Nantikan Mingmoon (International Journal of Renewable Energy Development, 2021)
This research study describes the preparation of corncob derivedactivated carbon to be used as anodematerial for the preparation of lithium ion battery.The corncob was activated at 900 °C for 3 hours with KOH used in a 1:3 weight ratio.The final product was analyzed for chemical, physical, and electrical properties.The results show that the activated carbon is amorphous and contains some graphitic carbon with interconnected nano-channels. Furthermore,carboxyl functional groups were detected on the surface of the activated carbon product.The observed morphological characteristics in terms of surface area, total pore volume, micropore volume, and average pore size are 1367.4501 m²/g, 0.478390 cm³/g, 0.270916 cm³/g, and 2.10872 nm, respectively.In addition, the product also exhibits low electrical resistance in the range 0.706W-1.071W.Finally, the specific discharge capacities at the 1st and the 2nd cycles of the corncob derived activated carbon anode material were 488.67mA h/g and 241.45 mA h/g, respectively with an average of about 225 Ah/kg between the 3rd cycle and the 5th cycle. The averagespecific charge capacities/specific discharge capacities at increasing charging rate of 0.2C, 0.5C, 1C, 2C, and 5C were approximated 190 mAh/g, 155 mAh/g, 135 mAh/g, 120 mAh/g, and 75 mAh/g, respectively, with 100%Coulombic efficiency in all 5 cycles.It was shown that the corncob derived activated carbon anode material has a relatively high rate capability, high reversibility, and rapid and stable capacity when compared to the general of biomass-derived carbon